De Novo Transcriptome Analysis of Polyunsaturated Fatty Acid Metabolism in Marine Protist Thraustochytriidae sp. PKU#Mn16. (7th November 2019) - Yang, Xuewei; Li, Siting; Li, Shuangfei; Liu, Liangxu; Hu, Zhangli
Abstract: Thraustochytriidae sp., have drawn the attention as a promising source for producing significant quantities of omega‐3 fatty acids. In this study, Thraustochytriidae sp. PKU#Mn16, with impressive docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) production, was de novo assembled as a complete transcriptome. A total of 59.65 Mb clean reads were assembled into 35, 745 transcripts, with a mean size of 991 bp. The results allowed us to annotate 11, 924 (45.97%) of the transcripts with putative functions. The potential target genes enriched for specific gene ontology terms, including metabolic process (469 genes) and macromolecular complex (221 genes), were identified. There were 6858 (26.44%) putative proteins classified into 25 categories, of which 459 (6.69%) predicted proteins were assigned to lipid transport and metabolism, closely related to DHA production. The most strongly represented pathways annotated from the kyoto encyclopedia of genes and genomes (KEGG) database were metabolism pathways including carbohydrate (388, 6.99%), amino acid (375, 6.76%), and lipid (330, 5.95%). Of these unigenes with coding sequences, the majority (2950) were 200–300 bp. A total of 7362 simple sequence repeats were identified with the frequency occurrence of 1/4.15 kb. This study reveals a wealth of the most comprehensive transcriptomic resource currently available for Thraustochytriidae sp., which could facilitate further research into the molecular mechanisms of fatty acid production.